Efficacy of omalizumab in chronic spontaneous urticaria refractory to conventional therapy: analysis of 110 patients in real-life practice. (September 2013) - Labrador-Horrillo, Moises; Valero, Antonio; Velasco, Manuel; Jáuregui, Ignacio; Sastre, Joaquin; Bartra, Joan; Silvestre, Juan Francisco; Ortiz de Frutos, Javier; Gimenez-Arnau, Ana; Ferrer, Marta
Abstract : Objective: To collect data on the efficacy and safety of omalizumab in 110 patients from 9 Spanish hospitals suffering from chronic spontaneous urticaria (CSU) refractory to conventional treatment. Methods: A retrospective, descriptive analysis was performed, showing the data of 110 patients suffering from refractory CSU who received omalizumab as an off-label treatment in 9 Spanish hospitals from October 2009 to September 2012. Results: Ninety (81.8%) patients exhibited a complete or significant response, 12 (10.9%) had partial response, and 8 (7.2%) showed no response. Sixty-six (60%) patients were able to stop all concomitant medications, remaining asymptomatic treated with omalizumab alone. No serious adverse events were reported. Conclusions: Omalizumab shows excellent efficacy and safety profile in a large series of CSU patients in real-life practice. This drug will contribute to settle the debt with CSU patients contributing to restore their quality of life.